PENDEKATAN INTERDISIPLINER PADA MATERI AKIL BALIG KELAS IV SD DALAM MATA PELAJARAN PAIBP - Fauzi, Akhmad; Syaibatul Hamdi Muzami, Fazrin; Alfian Shihabudin, Muhammad; Taupik Kurahman, Opik (As-Sulthan Journal of Education, 2026)
Learning of Islamic Religious Education and Character (Pendidikan Agama Islam dan Budi Pekerti/PAIBP) at the elementary school level requires the application of approaches that are not only normative and doctrinal but also contextual and aligned with students’ developmental stages. One of the essential topics in Grade IV is puberty (akil balig), which is closely related to students’ biological, psychological, social, and moral aspects. This topic requires a comprehensive learning strategy so that it can be understood appropriately and meaningfully. This article aims to examine the implementation of an interdisciplinary approach in teaching puberty material in the PAIBP subject for Grade IV elementary school students. The research method employed is a literature review by analyzing sources such as Islamic education books, PAIBP curriculum documents, and scholarly articles relevant to interdisciplinary approaches in education. The findings indicate that the interdisciplinary approach is able to integrate Islamic values with other disciplines, including Natural Sciences, Physical and Health Education, and Social Studies. Such integration makes puberty learning more holistic, contextual, and relevant to students’ developmental needs, while also helping students understand personal changes from both scientific and religious perspectives.